2014
DOI: 10.1039/c3fo60483g
|View full text |Cite
|
Sign up to set email alerts
|

Effect of dietary antioxidants on the cytostatic effect of acrylamide during copper-deficiency in Saccharomyces cerevisiae

Abstract: Acrylamide exposure increases oxidative stress and causes cytotoxicity. In order to understand the role of oxidative stress in acrylamide toxicity, we utilized Saccharomyces cerevisiae as a model organism grown in Yeast Peptone Dextrose (YPD) or Copper-Deficient Medium (CDM). Although the growth curves of yeast were comparable in these media, acrylamide treatment resulted in significant growth inhibition and colony formation only in the CDM. Copper-deficiency induced a decrease in the intracellular metallothio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 65 publications
1
6
0
Order By: Relevance
“…The inhibition of AA on yeast proliferation was mainly reflected in three aspects: firstly, it reduced the rate of yeast proliferation; secondly, the yeast inoculated in the medium containing AA had a longer lag phase; thirdly, the maximum density of yeast proliferation was significantly reduced. This result is consistent with the study on AA cytotoxicity using yeast as a model, but previous studies did not explore the effect of AA on the growth kinetics parameters of yeast [ 3 , 4 ].…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…The inhibition of AA on yeast proliferation was mainly reflected in three aspects: firstly, it reduced the rate of yeast proliferation; secondly, the yeast inoculated in the medium containing AA had a longer lag phase; thirdly, the maximum density of yeast proliferation was significantly reduced. This result is consistent with the study on AA cytotoxicity using yeast as a model, but previous studies did not explore the effect of AA on the growth kinetics parameters of yeast [ 3 , 4 ].…”
Section: Discussionsupporting
confidence: 91%
“…This inconsistency may be attributed to the following three aspects: different experimental models, different doses of AA, and different observation time points. In this study, SOD activity in the cells exposed to AA for 2 h was lower than that in the vehicle group, and the results obtained by using a lower dose of AA (about 14 mM) in similar studies were that SOD was activated [ 3 ]. Therefore, under the intervention of high concentration of AA, SOD activity will be inhibited.…”
Section: Discussionmentioning
confidence: 62%
See 2 more Smart Citations
“…; Kommuguri et al . ). Additionally, we have shown that the berry juices significantly protect both WT and Δ sod1 cells against an inhibition of growth caused by acrylamide.…”
Section: Resultsmentioning
confidence: 97%